Prevalence of Thyroid Disorders in Children at a Tertiary Care Hospital - Muhammad Punhal, Nusrat Ali, Saleh Jan, Alia Halim, Safia Bibi, Muhammad Gauhar Shabbir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Thyroid disorders are most common in children. Early diagnosis and management is crucial. Objective: The aim of this study was to find out the Prevalence of Thyroid Disorders in Children at a Tertiary Care Hospital. Materials and Method: The current retrospective study was carried out at the pediatric department of HBS General Hospital, Islamabad from July 2022 to June 2023, after taking approval from the ethical board of the institute. Children below 5 year old with thyroid dysfunction symptoms who visited the OPD and IPD of the hospital were included. A total 502 individuals were enrolled their demographic features were noted. The thyroid gland was examined in accordance with WHO recommendations. The thyroid profiles of all the participants were diagnosed, including the levels of, T4 and T3. The tests were used in this study were T3-ARCHITECT Total T3 assay (Abbott Diagnostics, reagent B7K640), TSH-ARCHITECT TSH assay (Abbott Diagnostics, reagent B7K620) & T4-ARCHITECT Total T4 assay (Abbott Diagnostics, reagent B7K660). Furthermore, children with hypothyroidism underwent testing and anemia grading using estimations of hemoglobin and RBC indices. When hypothyroidism manifested as a single thyroid nodule, FNAC of the thyroid gland was carried out. Data was entered to Microsoft excel and represented in frequency and percentage. Results: A total of 502 children below 12 years old were screened for thyroid disorders .out of which 69 (13.7%) were found to have thyroid dysfunction. the prevalence of hypothyroidism was observed in 63(91.3%) and 6(8.6%) had hyperthyroidism. Goiter was present in only 16% of individuals with thyroid dysfunction. Dwarfism was the most prevalent clinical manifestation (60%) and was followed by lethargy (50.7%) were noted in hypothyroid individuals. All the individuals with hyperthyroidism showed tachycardia while palpitation and heat intolerance were observed in 83. Anemia was observed in 20 (31.74%) of the hypothyroid children. There was no instance of thyroid gland cancer. Congenital heart disease was the most prevalent of the several co-morbidities found in 24 children with thyroid dysfunction. Conclusion: Our study concluded that the thyroid disorders are most prevalent in children (13.7%), and further studies of this kind from other parts of the country with larger populations are really needed Keywords: Thyroid disorders; Children; Prevalence.